Total cell N-glycosylation is altered during differentiation of induced pluripotent stem cells to neural stem cells and is disturbed by trisomy 21 - Ana Cindrić; Frano Vučković; Aoife Murray; Thomas S. Klarić; Ivan Alić; Jasminka Krištić; Dean Nižetić; Gordan Lauc (BBA Advances)
Down syndrome (DS), a genetic condition caused by trisomy 21 (T21), manifests various neurological symptoms, including intellectual disability, early neurodegeneration, and early-onset dementia. N-glycosylation is a protein modification that plays a critical role in numerous neurobiological processes and whose dysregulation is associated with a range of neurological disorders. However, whether N-glycosylation of neural glycoproteins is affected in DS has not been studied. To better understand how T21 affects N-glycosylation during neural differentiation, we utilized an isogenic in vitro induced pluripotent stem cell (iPSC) model of T21 in which both T21 and euploid disomic karyotype (D21) clones were obtained from a single individual with mosaic DS. We comprehensively characterized and compared the total N-glycomes of iPSCs and their neural stem cell (NSC) derivatives. N-glycomics analysis of whole cell lysates was performed using liquid chromatography coupled with tandem mass spectrometry to determine N-glycan structures. Our results show that neural differentiation of iPSCs to NSCs is characterized by an increase in the abundance of complex N-glycans at the expense of minimally processed mannosidic N-glycans. Moreover, we found differences in N-glycosylation patterns between D21 and T21 cells. Notably, the abundance of pseudohybrid N-glycans was significantly higher in T21 cells which also exhibited a significantly lower abundance of a specific hybrid monoantennary fucosylated N-glycan (H6N3F1). Overall, our data define the total N-glycome of both D21 and T21 iPSCs and NSCs and show that T21 already impacts N-glycosylation patterns in the stem cell state in a manner consistent with aberrantly premature neural differentiation of T21 cells.